Solar Stimulus: Perceptions of banks and credit unions towards solar loans in Massachusetts - Bahirwani, Suveer. (2017)
Abstract: Access to finance for residential solar photovoltaic systems (PV) is an essential element of the clean energy economy. Perceptions about solar PV and solar loans among lenders at banks and credit unions shape the availability of lending products for residential solar PV. In March 2015, interviews were carried out among select informants and subsequently, between April and May 2015, a survey was conducted to gauge the perceptions of lenders in Massachusetts. Lenders have a range of concerns with the market and the provision of solar loans. These concerns can be grouped around risk, market size or viability and policy uncertainty. In summary, lending for this segment is not a priority for banks and credit unions in Massachusetts at this time. Recommendations are offered for the lending community and policymakers to improve adoption. Questions for further research are also presented.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Penn Loh.; Keywords: Energy, Public policy, and Environmental economics.